The Influence of Promotion, Trust and Customer Experience on Customer Loyalty through Customer Satisfaction at LPK “Maju Jaya” in Grobogan - Rahayu, Sucik; Hwihanus, Hwihanus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The objective of this study is to demonstrate and evaluate the effects of customer satisfaction at LPK "Maju Jaya" in Grobogan, as well as consumer trust and customer experience, on customer loyalty. A sample of ninety LPK "Maju Jaya" consumers was taken. Research of this kind is quantitative in nature. The data analysis tool utilized is SMART PLS. According to this research, promotion, trust and customer experience have a positive influence and influence on satisfaction. Although customer experience and satisfaction have a positive and significant influence on loyalty, they do not have a positive and significant influence on loyalty. In addition, it has a positive and significant impact on loyalty through customer satisfaction, advertising, trust and experience.